O plágio acadêmico na percepção de estudantes universitários - Lima, Thaís Aparecida de (Universidade Federal de São Carlos, 2019)
The definition of Information Literacy is related both to the set of knowledge, skills and attitudes that individuals must possess to use information in a critical and ethical way, as well as lifelong learning. The ethical dimension of Information Literacy is based on the behavior that reachs the worry with legal aspects about the use of information by the individual for the realization of the collective good. The use of information and communication technologies and the ease of access to a large amount of information makes even more relevant the issues of the adequate use of information sources and the ethical dimension of Information Literacy to combat plagiarism for the legal use of information. The present work aims to verify the perception that undergraduate members of an academic community have regarding academic plagiarism based on the ethical use of information in the context of Information Literacy, addressing the issue of plagiarism. The research developed has a quantitative-qualitative character, based on a bibliographical review of the topics addressed, and it was exploratory in relation to the research objectives. To collect data and present the results, a questionnaire was applied to university students on the Bachelors Degree in Library and Information Science (BCI) and Biological Sciences, at the Federal University of São Carlos (UFSCar). The research results allowed us to identify that: respondents can understand what plagiarism is, but from the responses chosen regarding the sanctions to be applied, most of them do not identify plagiarism as a crime of copyright infringement. And although most respondents stated that they cite the sources used in their academic work, the consistency of the citation may be impaired due to the lack of frequency in consulting referencing and bibliographic standards. Finally, we identified that within the university, initiatives to tackle plagiarism are still incipient and the issue requires further debate and reflection therein.
Academic plagiarism from the perspective of university students
Keywords: Competência informacional; Ética na pesquisa; Plágio acadêmico; Information literacy; Research ethics; Academic plagiarism; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA